Creating a Video for TikTok Social Media Content Kelirskin with the Theme of Balinese Kecak Dance Local Wisdom - Azizi, Jovita Nabilah; Damara, Rafli; Holik, Wildan; Fami, Amata; Barus, Irma Rasita (Politeknik Negeri Media Kreatif, 2024)
The use of social media, especially TikTok, has become an integral part of digital marketing strategies for many brands, including Kelirskin. In this study, we explore the potential of TikTok as an effective marketing tool to boost Kelirskin product sales with a focus on the theme of Balinese Kecak dance local wisdom. Through pre-production, production, and post-production stages, we designed and created promotional videos that combine the beauty of Bali's nature and culture with the messages inherent in the Kelirskin brand. Despite facing some challenges, such as selecting appropriate settings and proper lighting, the authors successfully overcame these obstacles with creativity and dedication from the production team. By implementing additional strategies, such as researching TikTok user trends, collaborating with influential users, and utilizing TikTok's interactive features, Kelirskin can maximize TikTok's potential as an effective marketing tool to boost their product sales and strengthen their brand position in the digital marketing market.